2018
DOI: 10.3916/c56-2018-08
|View full text |Cite
|
Sign up to set email alerts
|

Spies and security: Assessing the impact of animated videos on intelligence services in school children

Abstract: Making the work of security organizations known to school children is a means of mitigating feelings of insecurity provoked by the diffusion of information on terrorist attacks in communications media and through social media. Whilst there is a longer tradition of projects to educate school children on the police and the armed forces, no comparable projects have been found on the intelligence services. With the objective of filling this gap, the authors designed and produced two animated educational videos for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 34 publications
0
1
0
Order By: Relevance
“…In addition, some studies have shown that a platform like YouTube can become a hub to work on reducing stereotypes in education (Díaz-Fernández & del Real-Castrillo, 2018) or encouraging digital practices aimed at preventing gender-based violence (Morales, Aran-Ramspott, & Fedele, 2020). However, no research works have thoroughly dealt with a potential gender gap among EduTubers as a group so far, a lack that this work sets out to address.…”
Section: The Gender Gap In the Field Of Education And Communicationmentioning
confidence: 99%
“…In addition, some studies have shown that a platform like YouTube can become a hub to work on reducing stereotypes in education (Díaz-Fernández & del Real-Castrillo, 2018) or encouraging digital practices aimed at preventing gender-based violence (Morales, Aran-Ramspott, & Fedele, 2020). However, no research works have thoroughly dealt with a potential gender gap among EduTubers as a group so far, a lack that this work sets out to address.…”
Section: The Gender Gap In the Field Of Education And Communicationmentioning
confidence: 99%